EXTRACTION AND CHARACTERIZATION OF FUNCTIONAL PROPERTIES OF CARRAGEENAN Kappaphycus alvarezii FROM COAST OF KUTAI TIMUR DISTRICT - Andi Noor Asikin; Indrati Kusumaningrum; Doddy Sutono (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Carrageenan is a gelling form of polysaccharide obtained from extraction process of red seaweeds (Rhodophyceae) including Kappaphycus alvarezii. Carrageenan is widely used for pharmacy, cosmetics, food, gelling, and binding agent as well as emulsifier and stabi-lizer. The quality of carrageenan is affected by several factors, one of them such as concen-tration of KOH. The objectives of this research were to define the best concentration of KOH for extraction and characterize the functional properties. Functional properties of carrageen-an in this research were sulphate content, acid insoluble ash, gell strength, fiber, and whiteness. The experimental design used for this research was completely ran-domized design with four treatments of KOH concentrations i.e. 1%, 3%, 5%, and 7%. The study showed that the use of KOH concentarion of 7% resulted the best of carrageenan quality containing 24.36% sulphate, 1.96% acid insoluble ash, 17.80 g/cm2 gell strength, 8.94% fiber and 58.91% whiteness. Keywords: carrageenan, extraction, functional properties, Kalium Hydroxide, Kappaphycus alvarezii